The Right vs. the Good: Kant vs. Rawls - Kitcher, Patricia (Studia Kantiana, 2023)
Rawls regarded the priority of the right over the good as the characteristic feature of Kantian constructivism. I have four goals in the paper. First, I try to refute Rawls’s reading of Kant on the relation between the right and the good. Second, I fill out Kant’s picture of the rational natures that have intrinsic value: They have the law of duty within, are predisposed to respect themselves and others who have the law of duty within, and belong to a community of rational natures. Third, I argue that because Kant thought that the right and the good were coeval, he is not a constructivist, but a kind of realist. Finally, I use my examination of the good, the intrinsically valuable in Kant, to reject any temptation to regard his ethics as dependent on his teleological claim that human nature is the end of nature.